2020
DOI: 10.1080/17435390.2020.1736355
|View full text |Cite
|
Sign up to set email alerts
|

Organ burden of inhaled nanoceria in a 2-year low-dose exposure study: dump or depot?

Abstract: No detailed information on in vivo biokinetics of CeO 2 nanoparticles (NPs) following chronic low-dose inhalation is available. The CeO 2 burden for lung, lung-associated lymph nodes, and major non-pulmonary organs, blood, and feces, was determined in a chronic whole-body inhalation study in female Wistar rats undertaken according to OECD TG453 (6 h per day for 5 days per week for a 104 weeks with the following concentrations: 0, 0.1, 0.3, 1.0, and 3.0 mg/m 3 , animals were sacrificed after 3, 12, 24 months). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Precipitation and formation of cerium phosphate particles might contribute to the slow clearance of nanoceria from the lung reported in [4,9,51,61]. Cerium ions, introduced as such or released during nanoceria dissolution, in the presence of phosphate form cerium phosphate [48,52,[62][63][64] as was reported after introduction of cerium ions into the lung [65].…”
Section: Role Of Phosphate In the Fate Of Cerium/ Nanoceriamentioning
confidence: 85%
See 2 more Smart Citations
“…Precipitation and formation of cerium phosphate particles might contribute to the slow clearance of nanoceria from the lung reported in [4,9,51,61]. Cerium ions, introduced as such or released during nanoceria dissolution, in the presence of phosphate form cerium phosphate [48,52,[62][63][64] as was reported after introduction of cerium ions into the lung [65].…”
Section: Role Of Phosphate In the Fate Of Cerium/ Nanoceriamentioning
confidence: 85%
“…After systemic administration of solvothermally synthesized nanoceria, cerium phosphate particles were seen in rat liver and spleen [48,63]. After inhaling 3 mg/m 3 NM-212 for two years, CeO + and CePO 4 + were seen in rat femur [9]. These studies demonstrate a certain extent of dissolution of both nanoceria [66,69]).…”
Section: Role Of Phosphate In the Fate Of Cerium/ Nanoceriamentioning
confidence: 94%
See 1 more Smart Citation
“…The ICP-MS organ burden data also exhibited high interlaboratory reproducibility: Upon 28-day exposure to 50 mg m −3 BaSO 4 NM-220 in female Wistar rats, a lung burden of ≈840 ± 180 µg was recorded (Table 1 and ref. [17]). Schwotzer et al [46] reported a rat lung burden of 1078 ± 197 µg after 28-day exposure to 50 mg m −3 of the same batch of BaSO 4 NM-220, that is, only 28% higher.…”
Section: Technical and Biological Variability Of The Lung Burden Datamentioning
confidence: 99%
“…Note that this comparison should be done at lung burdens that do not induce lung toxicity, as this usually reduces lung clearance. A factor of 2-fold reflects the limited precision of half-time measurements (few time points, individual, intra-experimental and interexperimental variability, limited analytical precision) (Tentschert et al 2020).…”
Section: Thresholds For In Vivo Testingmentioning
confidence: 99%